Walking the Tightrope: The President’s Council, P.W. Botha and the Rhetoric of Reform (Historia, 2023)
The response by P.W. Botha to the economic crisis, civil unrest and international condemnation affecting South Africa in the 1970s and 1980s was described as his ‘total strategy’. An aspect of this was a process of reform in the system of apartheid in order to meet the challenges to modernisation and economic development. The President’s Council was an advisory body established by Botha to investigate and make recommendations regarding reform in the socio-economic and political spheres, which were undermining apartheid ideology of racial segregation. Comprising five committees with delegates drawn from diverse sectors of the South African population, the President’s Council published several reports identifying the challenges facing South Africa and the means by which it hoped to address them. The reports focused on education, demography, black urbanisation, discriminatory legislation and constitutional reform. A hitherto largely neglected source, these reports and their ideological and intellectual influences are analysed in this article so as to assess the possibilities and limitations of Botha’s reforming initiative.
Keywords: President's Council; P.W. Botha; apartheid; reform; modernisation; 'total strategy'